Bibliometric analysis of scientific articles of jurimetry published in Brazil - Maia, Marcos (2020)
Judicial delays have been the subject of debate in the Brazilian academic community. Among the solutions discussed, jurimetrics has gained ground in seeking quantitative standards in court decisions. However, despite the relevance of this methodology, in Brazil, few researches have been conducted towards its dissemination. Therefore, the present study employs bibliometric techniques on national scientific production, related to the term “jurimetrics”, from 2002 to 2019, available in the Google Scholar database, presenting an informative panel about the characteristics (author, citations, keywords, magazines) found in these publications. The results show that in the surveyed period, the number of publications on the subject presented an average annual growth of 18.92%. The collaboration index indicates that there are, on average, 2.32 authors per article, some of which stand out for the number of publications, among them, Daniel F. N. Menezes (four) and Filipe J. Zabala (three) and, in turn, the most cited authors are Lee Loevinger (seven citations), Filipe J. Zabala and Fabiano F. Silveira (both with six citations); the magazine that has published most on the subject is the Revista da Faculdade de Direito da Universidade Federal de Minas Gerais, while a single magazine published four articles, seven magazines two articles and 56 magazines a single article and, finally; as for the keywords associated with the term, "adoption" and "civil procedure" stands out.